2008
DOI: 10.1080/02841850802452075
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal mammography and sonography associated with foreign-body giant-cell reaction after stereotactic vacuum-assisted breast biopsy with carbon marking

Abstract: In four of 130 lesions (3%) that were carbon marked following stereotactic vacuum-assisted breast biopsy, and in which surgical excision was not required, the mammographic and ultrasound follow-up appearance of the breast simulated malignancy. The abnormality was attributable to the use of carbon, which represents a potential source of misdiagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…69 No interaction of the suspension with histopathological assessment has been reported. Of note, however, in a retrospective series by Ruiz-Delgado et al, 72 in which 130 patients who underwent charcoalsuspension localization and excision were followed up at 1 year after surgery with mammography, 4 patients were identified with suspicious radiological images (spiculated masses). Histopathological analyses demonstrated foreign-body giant-cell reaction attributable to charcoal in all 4 patients, 72 which emphasizes the need to remove all charcoal suspension, including the injection tract, during surgery.…”
Section: Magnetically Guided Localizationmentioning
confidence: 98%
“…69 No interaction of the suspension with histopathological assessment has been reported. Of note, however, in a retrospective series by Ruiz-Delgado et al, 72 in which 130 patients who underwent charcoalsuspension localization and excision were followed up at 1 year after surgery with mammography, 4 patients were identified with suspicious radiological images (spiculated masses). Histopathological analyses demonstrated foreign-body giant-cell reaction attributable to charcoal in all 4 patients, 72 which emphasizes the need to remove all charcoal suspension, including the injection tract, during surgery.…”
Section: Magnetically Guided Localizationmentioning
confidence: 98%
“…Because of the stability of the charcoal powder, a delayed surgery after the localization procedure is possible; on the contrary, methylene blue has a fast dispersion in the tissue. A potential disadvantage of carbon marking is obstruction of needle tip due to precipitation of charcoal particles [35]; moreover, foreign-body giant-cell reactions mimicking malignancy have been reported after vacuum-assisted breast biopsy with carbon marking [36]. Rose et al reported in a comparison study between carbon marking and wire-guided excision a close or involved margins rate of 18.9% (27/143) with the former technique [37].…”
Section: Preoperative Localization Techniquesmentioning
confidence: 99%
“…ROLL is most accurate (up to 94% clear margins) but is expensive, not universally available, and carries risks associated with radioactive tracers, especially if dispersed widely after accidental intraductal injection [25,59,60]. Carbon marking is less accurate (80% clear margins) and foreign-body reactions may mimic malignancy on follow up imaging [61,62]. Clip marking at the time of biopsy is particularly useful in the setting of neoadjuvant chemotherapy, where the tumour may regress and become invisible on conventional imaging [63].…”
Section: Discussionmentioning
confidence: 99%